2001
DOI: 10.4049/jimmunol.167.7.3962
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced Increase of Prostaglandin E2 Is Mediated by Inducible Nitric Oxide Synthase Activation of the Constitutive Cyclooxygenase and Induction of Membrane-Associated Prostaglandin E Synthase

Abstract: NO produced by the inducible NO synthase (NOS2) and prostanoids generated by the cyclooxygenase (COX) isoforms and terminal prostanoid synthases are major components of the host innate immune and inflammatory response. Evidence exists that pharmacological manipulation of one pathway could result in cross-modulation of the other, but the sense, amplitude, and relevance of these interactions are controversial, especially in vivo. Administration of 6 mg/kg LPS to rats i.p. resulted 6 h later in induction of NOS2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…TNF-␣ up-regulation of COX-2 and mPGES-1 was attenuated and augmented by interferon-␥, respectively (Wright et al, 2004). Induction of mPGES-1 by LPS (Devaux et al, 2001;Uematsu et al, 2002) was shown to be mediated by the Toll-like receptor 4/MyD88/NF-IL-6-dependent signaling pathway (Uematsu et al, 2002) and could be augmented by 9-cis-retinoic acid (Tsukamoto et al, 2004).…”
Section: G Regulation and Gene Structurementioning
confidence: 99%
“…TNF-␣ up-regulation of COX-2 and mPGES-1 was attenuated and augmented by interferon-␥, respectively (Wright et al, 2004). Induction of mPGES-1 by LPS (Devaux et al, 2001;Uematsu et al, 2002) was shown to be mediated by the Toll-like receptor 4/MyD88/NF-IL-6-dependent signaling pathway (Uematsu et al, 2002) and could be augmented by 9-cis-retinoic acid (Tsukamoto et al, 2004).…”
Section: G Regulation and Gene Structurementioning
confidence: 99%
“…PCR amplification was performed by the hot starting method, using Takara Best RT-PCR (Takara). The sequences of primers used in this study were designed according to the published study (Devaux et al, 2001). The sequences of sense and antisense primers for the rat COX-2 were 5Ј-TTCAAAAGAAGTTCTGGAAAAGGT-3Ј and 5Ј-GATCATGTC-TACCTGAGTGTCTTT-3Ј, respectively, giving rise to 304-bp PCR product.…”
Section: Methodsmentioning
confidence: 99%
“…These in vitro experiments suggest that NO has the ability to lead the COX enzyme to two opposed states; activation or inactivation, depending on cell types used or experimental conditions. Several studies performed in vivo are also controversial with respect to the interaction of NO with COX activity (Paya et al, 1997;Hamilton and Warner, 1998;Devaux et al, 2001). In these studies, the iNOS inhibitors with different selectivity were used, and NO production was evaluated indirectly by measuring plasma or urinary levels of nitrite plus nitrate, which can be derived not only from endogenously produced NO but also from nitrate in a diet.…”
Section: Effect Of Cox Activity On No Production By Inos 999mentioning
confidence: 99%
“…In airway macrophages, NO may in fact act on 5-LO and suppress LT synthesis (Coffey et al, 2000(Coffey et al, , 2002. The actions of NO on the COX pathway have not been completely elucidated but apparently involve both direct and indirect mechanisms (Salvemini et al, 1993;Watkins et al, 1997;Devaux et al, 2001).…”
mentioning
confidence: 99%